Mediation, conciliation and transaction in the collection of tax due as a procedure to protect the personality rights of vulnerable taxpayers (Revista Direito em Debate, 2023)
This article seeks to investigate the critical scenario in which the tax execution procedure are currently pending in the Judiciary are found, as well as to verify the possibility and legitimacy of the adoption of consensual instruments such as mediation and conciliation in the solution of conflicts in tax matters. Therefore, the nature of the tax credit is investigated in view of the unavailability of the public interest. It is understood that mediation and conciliation are a suitable alternative instrument for collecting the tax credit, since it is the property of the tax authorities, who may dispose of it. The possibility of including these instruments in the tax execution procedure is based on their effects on the protection and guarantee of personality rights, such as privacy and honor, of the taxpayers who are in a position of vulnerability. Through bibliographic research and the hypothetical-deductive method, the impacts of the participation of the parties will be evaluated in the tax dispute, as well as will be analyzed how mediation and conciliation can contribute to resolve the constant inequalities in the legal-tax relationship and, at the same time, favor the effectiveness of the State's performance.